Analisis Penilaian Risiko Kebakaran sebagai Upaya Pengendalian pada Gedung SMAN 1 Cisarua Kabupaten Bogor - Deurratu Syatila Sabrina; Eka Fitriani Ahmad; Muhammad Islam Nasution (Jurnal Pengembangan Ketenagakerjaan, 2025)
School buildings are not immune to the risk of fire. Based on national statistics from 2024, fire was the most frequent disaster, occurring 935 out of 2,408 times. This study was conducted to determine the probability of fire hazards in school buildings and how to control them. The analysis was conducted based on the five stages of the Fire Risk Assessment (FRA): hazard identification, identification of people at risk, risk evaluation and control, documentation and training, and review. The results showed that fire protection facilities, such as portable fire extinguishers (APAR), were available but poorly maintained and not regularly tested, while other fire protection systems were not yet in place. The school lacked a documented emergency plan, and evacuation simulations had never been conducted comprehensively, thus failing to comply with applicable regulations. As a sustainable mitigation effort, an evaluation of the fire risk assessment is recommended to systematically strengthen the fire protection system, develop fire evacuation procedures, and provide regular training for the entire school community.